Analysis of Indonesia’s Railway Track Structure Behavior Under Double-Stack Freight Train Loading - Hanafi Isnanta Prabawa (International Journal of Sustainable Construction Engineering and Technology, 2023)
The growing number of freight transported using railway transport is massive. Indonesia targeted 995,500,000 tons of freight transported using the railway mode. Double-stack train is one solution to increase the freight tonnage of the train without adding the number of operations of the train. The 3D ANSYS model is made to see the structural behavior of railway tracks under the double-stack train load using 1067 mm and 1435 mm gauge from Indonesia’s railway track regulation. It was also modeled with several speeds to observe its influence on the structure. It is known that in all output parameters of deformation, stress, and strain, the 1435 mm gauge acts better for the structure than the 1067 mm gauge. The subgrade service life also became longer in the 1435 mm gauge structure. Lower speed also gives a better impact on the structure of the track and possible to give longer service life for subgrade. Further research is needed to observe the railway track structural behavior in cyclic loading and the possibility of reinforcing the subgrade. The lab-scale test also needed to validate the analysis.